Direct purification of Burkholderia Pseudomallei lipase from fermentation broth using aqueous two-phase systems. - Ooi, Chien Wei; Tey, Beng Ti; Hii, Siew Ling; Ariff, Arbakariya; Wu, Ho Shing; Lan, John Chi Wei; Juang, RueyShin; Mustapa Kamal, Siti Mazlina; Chuan, Ling Tau (Springer, 2009)
An aqueous two-phase purification process was employed for the recovery of Burkholderia Pseudomallei lipase from fermentation broth. The partition behavior of Burkholderia Pseudomallei lipase was investigated with various parameters such as phase composition, tie-line length (TLL), volume ratio (VR), sample loading, system pH, and addition of neutral salts.Optimum conditions for the purification of lipase were obtained in polyethylene glycol (PEG) 6000-potassium phosphate system using TLL of 42.2% (w/w), with VR of 2.70, and 1% (w/w) NaCl addition at pH 7 for 20% (w/w) crude load. Based on this system, the purification factor of lipase was enhanced to 12.42 fold, with a high yield of 93%. Hence, the simplicity and effectiveness of aqueous two-phase systems (ATPS) in the purification of lipase were proven in this study.